PENDAMPINGAN PEMERIKSAAN HEWAN DAN DAGING QURBAN DI MASA PANDEMI COVID-19: Assistance In The Examination Of Animal And Qurban Meat During The Covid-19 Pandemic - Freshinta Jellia Wibisono; Lailia Dwi Kusuma Wardhani; Retina Yunani; Adhitya Yoppy Ro Candra; Asih Rahayu; Bagus Uda Palgunadi; Nurul Hidayah; Desty Apritya; Dyah Widhowati; Era Hari Mudji (IGKOJEI: Jurnal Pengabdian Masyarakat, 2022)
Slaughtering of sacrificial animals is a worship activity for slaughtering ruminant livestock which is carried out on Eid al-Adha and carried out in mosques or outside Slaughterhouses (RPH). The limited facilities affect the welfare of the animals so that it affects the quality of the meat. Supervision in the production chain with antemortem and postmortem inspections is carried out to obtain good quality meat. This community service aims to help the community get a guarantee of safe, healthy, whole and halal, sacrificial animal meat with antemortem and postmortem examinations, as well as holding counseling on the handling of sacrificial animals and meat during the covid-19 pandemic through webinars. The activity was carried out in 13 mosques in the areas of Surabaya, Sidoarjo, Gresik, and Pasuruan. The antemortem examination will be held on 19-22 July 2021 followed by a post-mortem examination which will be held on 20-22 July 2021 with a total number of 112 cows, 220 goats and 1 sheep. The Webinar was held earlier, namely on July 14, 2021, by 3 competent speakers. The webinar was attended by the general public, mosque takmir, lecturers, and students. The results of the antemortem examination indicated that the animals were suitable for slaughter, although 2–6 (0.6–1.8%) animals showed diarrhea, nasal and eye discharge, and infection of the prepuce. The results of postmortem examination stated that the animals were fit for consumption with a note that the organs infected with worms had to be removed, namely 15.2% of the liver of cattle and 0.9% of the liver of goats with fasciolosis, 0.5% of goats experiencing parampistomiasis and 1.7% of cattle experiencing eurytrematosis.